The prevalence of malnutrition based on anthropometry among primary schoolchildren in Binh Dinh province, Vietnam in 2016 - Truong Quang Dat; Le Nguyen Huong Giang; Nguyen Thi Tuong Loan; Vo Van Toan (AIMS Press, 2018)
Objective: The study was conducted to determine the prevalence of malnutrition based on anthropometry among primary schoolchildren in Binh Dinh province, Vietnam. Material and Methods: This was a school-based cross-sectional survey using random sample technique with multistage process. Variables in malnutrition were classifed as thinness, stunting, underweight, overweight, and obesity based on z-scores according to the World Health Organization (WHO) (2007). Anthropometric measurements were taken according to WHO's standard procedures. The Chi-square test was used to compare prevalences and the Chi-square test for trend was employed to assess the trend of the prevalence of malnutrition forms by age. Results: 6,514 pupils from 6 to 10 years old including 3,298 males and 3,216 females were observed. The prevalence of thinness, stunting, underweight, overweight and obesity among schoolchildren accounted for 11.19%, 6.16%, 10.79%, and 30.1%, respectively. The prevalence of underweight and that of overweight-obesity of all pupils at the age of 6 were 13.1% and 32.11%, respectively, and tended to decrease to age 10 (p < 0.01). The prevalence of thin and stunted pupils had little sign of change over ages (p > 0.05). There was a statistically significant difference in the prevalence of malnutrition in three areas of Binh Dinh (p < 0.05), in which the highest prevalence of undernutrition was in mountainous area and midland, and the highest prevalence of overweight-obesity was in urban areas. Conclusion: The prevalence of malnutrition of primary schoolchildren in Binh Dinh was relatively high, in which the prevalence of overweight-obesity was rather high in urban areas and the prevalence of undernutrition was pretty high in mountainous area and midland. This study has characterized an important public health challenge, highlighting the need for attention to potential interventions.